2008
DOI: 10.1007/s12265-008-9072-7
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Basis of Thrombosis and Bleeding in Patients with Ventricular Assist Devices

Abstract: The clinical success of left ventricular assist devices (LVADs) has been tempered by significant hemorrhagic and thromboembolic complications. In the case of LVADs, where the biomaterial is in direct contact with the blood circulation, significant changes in systemic immunologic and thrombostatic functions have been well documented. Although further investigation is warranted, significant advances have been made in both cellular biology and LVAD technology to better understand the delicate balance between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…However, nonocular bleeding complications with both the traditional pulsatile LVAD and the newer continuous-flow LVAD have been reported. 6,7 Angiodysplasia and AVMs are common sources of GI bleeding, which had previously occurred in our patient as well.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, nonocular bleeding complications with both the traditional pulsatile LVAD and the newer continuous-flow LVAD have been reported. 6,7 Angiodysplasia and AVMs are common sources of GI bleeding, which had previously occurred in our patient as well.…”
Section: Discussionsupporting
confidence: 62%
“…The ocular bleed in this patient likely resulted from the change in systemic immunologic and thrombostatic function from direct contact of the blood circulation with the LVAD biomaterial. 7 Though the mildly elevated INR may have contributed to the intraocular bleed, at least one study showed that INR was not predictive of bleeding events after LVAD implantation. 11 Another study indicated that older age (>65), lower preoperative hematocrit (≤31), ischemic cardiomyopathy, and female sex were risk factors for bleeding with the LVAD.…”
Section: Discussionmentioning
confidence: 99%
“…1 There are multiple emerging theories as to why this is the case, including reduced arterial pulse pressure promoting AVM formation, as well as the development of an acquired von Willebrand syndrome. 2 The lowered pulse pressure secondary to continuous-flow device therapy is akin to patients with severe aortic stenosis (AS). Heyde first described this association with AS in 1958.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include interaction of the blood with artifi cial surfaces, mechanical effects on coagulation factors, and high fl ow rates through small gaps, such as those within continuous fl ow devices, that may lead to high shear forces on the blood. 36,37 Excessive shear can lead to platelet degradation and dysfunction as well as destructi on of other blood factors, such as von Willebrand factor. 36 Antiplatelet therapy may be more important to use with these devices than anticoagulation therapy, but it is not yet clear at which point these shear stress-induced abnormalities develop, or what the optimal management strategies should be.…”
Section: Cannula Obstructionmentioning
confidence: 99%